Rethinking firm-specific advantages from intellectual property rights: Boundary conditions for MNEs - Prud’homme, Dan; Tong, Tony W. (Journal of International Business Studies, 2024)
We develop three sets of theoretical boundary conditions for the firm-specific advantages (FSA) and country-specific advantages (CSA) view of intellectual property rights (IPR) in international business. These conditions explain when and where MNEs’ FSAs accrued from IPR assets (IPR-FSAs) are larger or smaller. In terms of IPR assets’ structure, we explicate the conditions creating complementarity problems among MNEs’ IPR that make IPR-FSAs larger, and the conditions under which complementarity problems between MNEs’ IPR and closely related legal rights make IPR-FSAs smaller. In terms of IPR assets’ geographic deployability, we explicate the rare conditions under which certain IPR-FSAs are non-location bound. However, we also explain that most IPR-FSAs are quasi-location-bound, and sometimes can even be fully location-bound, and therefore are smaller for MNEs’ units abroad. In terms of IPR assets’ defensibility, we explicate the conditions allowing IPR to still afford FSAs to MNEs even if the IPR cannot be favorably enforced. We argue that integrating these conditions into the FSA–CSA framework enables it to more precisely explain when and where there are heterogeneities in the size of MNEs’ IPR-FSAs. We also explain how our work can facilitate the empirical study of IPR-FSAs in international business research and guide MNEs’ IPR strategies.